ANTECEDENTS OF ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AMONG PUBLIC / CIVIL EMPLOYEES: A SCOPING REVIEW - Razima Hanim Osman; Mariny Abdul Ghani; Norzaliza Alis (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Organizational citizenship behaviour (OCB) throughout literature provides evidence in increasing organizational welfares as well as its employees’ welfares. It is important to understand the reasons behind the occurrence of OCB in order to increase the likelihood of employees to engage in OCB. Moreover, it is important for public/ civil employees to engage in OCB as they provide services to meet societal needs and demands. The present article set out to analyze the existing literature on the OCB’s antecedents among public/ civil employees in Asian contexts. Guided by the scoping review method, a review of the SCOPUS, ProQuest and MyJurnal databases identified 20 related studies. Further review of these studies resulted in categorizing the antecedents in three settings - law enforcement and military settings, nurses and public health settings and lastly office-based settings. The antecedents were discussed based on the four main domains - employee characteristic, task characteristics, organizational conditions, and leadership behaviour. The review also suggests to investigate further and integrated with other variables which moderating or mediating the relationships between the antecedents and OCB.